The 22nd And 25th Amendments: Constitutional Succession And Presidential Term Limits - Badawi, Habib (Limbago: Journal of Constitutional Law, 2026)
This study examines the constitutional tension between the 22nd and 25th Amendments to the United States Constitution, analyzing how their structural interaction creates pathways through which presidential term limits may be circumvented through non-electoral succession mechanisms. Integrating constitutional institutionalism, democratic consolidation theory, and power distribution theory, the study conducts a comparative analysis of the two amendments' divergent constitutional grammars—the 22nd Amendment's prohibition on being "elected" more than twice versus the 25th Amendment's mechanisms for "acting as" or "becoming" President through non-electoral succession—and of the 12th Amendment's eligibility clause that constitutionally bridges them. Drawing on American historical precedents and comparative evidence from Latin American presidential systems, the analysis develops a typology of three constitutional succession variants through which a twice-elected president might reassume executive authority without a new electoral mandate, evaluating each through the triadic analytical framework. The study concludes that the 25th Amendment's institutional plasticity represents a constitutionally distinct and structurally more tractable pathway for executive influence than the 22nd Amendment's default-rule design contemplated, and proposes constitutional and legislative reforms to close the inter-amendment gap.